Estudio teórico-experimental de un sistema mecánico para evitar caídas en una motocicleta Baja Pulsar 180 durante el proceso de aprendizaje - Cano Espinoza, Ricardo Gabino (2018)
The present thesis project consists in the experimental theoretical study of a mechanical system that avoids falls in the learning of driving in a motorcycle brand Bajaj model Pulsar 180. Identifying the scenarios, a series of demands and requirements were established for the design and operation of the mechanical system, where the most relevant were: low cost, ease of assembly, and manufacturing with standard materials. Once the problem and the hypothesis were defined, two evaluations were determined to obtain the optimal design of the mechanical system, then followed with the construction of a prototype. The first evaluation consisted of the initial concept of the solution, where the technical and economic criteria of the possible designs of the mechanical system were evaluated, making a morphological matrix and resulting in two preliminary solution projects. The second evaluation consisted of the optimal project of the mechanical system, where the preliminary solution projects were evaluated using the Cartesian coordinate method. With the optimal design, we proceeded to analyze the design by the finite element method, for which the Nastran IN CAD engineering software was used, after carrying out the theoretical study, we proceeded to build the prototype mechanical system, and conducted an experimental test to evaluate the resistance and performance of the prototype in the field. After the experimental evaluation of the prototype mechanical system, and to modify mechanical details in the mechanism, a stable prototype was obtained which has results of high degrees of reliability. To detail the components of the prototype mechanical system, the manufacturing drawings were made, which are presented in the present thesis. Finally, the thesis project proposes that the mechanical system developed can be improved in future research and be considered in safety systems in the learning of motorcycle driving.